Boundary lubricity of phosphonium bisoxalatoborate ionic liquids. (September 2021) - Rohlmann, Patrick; Watanabe, Seiya; Shimpi, Manishkumar R.; Leckner, Johan; Rutland, Mark W.; Harper, Jason B.; Glavatskih, Sergei
Abstract: The lubricating performance of trihexyl(tetradecyl)phosphonium bisoxalatoorthoborate (P-BOB) ionic liquid is analysed at 80 °C and 140 °C, and compared to an ionic liquid containing a partially hydrated version of the anion. The reduction of the anions produces oxalate complexes that contribute synergistically to lower friction. The role of oxalate in enhancing lubricity was indicated by the fact that the partially hydrated anion is a precursor orthoborate anion complexed with oxalic acid. It consequently showed the lowest friction at 80 °C. Upon heating, the precursor was converted into [BOB] − and displayed the same friction at 140 °C as the fully synthesised species. The mechanisms of the breakdown of the [BOB] − anion and formation of the tribofilm are elucidated. Graphical Abstract: ga1 Highlights: Ionic liquid significantly reduces friction compared to mPAO. Lubricity of the ionic boundary layer is enhanced by the oxalate dianions. Thermal conditions and water influence the amount of oxalate in the contact. Adsorbed layers are reinforced by tribofilms containing boron and phosphorous. The reaction mechanisms of ionic liquids in the lubricated contact are examined.